Characterizing Insertion Pressure Profiles During Cochlear Implantation: Simultaneous Fluoroscopy and Intracochlear Pressure Measurements. Issue 1 (January 2020) - Gonzalez, Joseph R.; Cass, Nathan D.; Banakis Hartl, Renee M.; Peacock, John; Cass, Stephen P.; Greene, Nathaniel T.
Abstract : Background: Combined electrical-acoustical stimulation (EAS) has gained popularity as patients with residual hearing are increasingly undergoing cochlear implantation. Preservation of residual hearing correlates with hearing outcomes, but loss of hearing occurs in a subset of these patients. Several mechanisms have been proposed as causing this hearing loss; we have previously described high amplitude pressure transients, equivalent to high-level noise exposures, in the inner ear during electrode insertion. The source of these transients has not been identified. Methods: Cadaveric human heads were prepared with an extended facial recess. Fiber-optic pressure sensors were inserted into the scala vestibuli and scala tympani to measure intracochlear pressures. Two cochlear implant (CI) electrode styles (straight and perimodiolar) were inserted during time-synced intracochlear pressures and video fluoroscopy measurements. Results: CI electrode insertions produced pressure transients in the cochlea up to 160 to 170 dB pSPL equivalent for both styles, consistent with previous results. However, the position of the electrode within the cochlea when transients were generated differed (particularly contact with the medial or lateral walls). Conclusions: These results begin to elucidate the insertion pressure profiles of CI electrodes, which can be used to improve CI electrode designs and facilitate "silent-insertions" to improve chances of hearing preservation.